Volumetric error compensation of machine tool using laser tracer and machining verification - Zha, Jun; Wang, Tao; Li, Linhui; Chen, Yaolong (International journal of advanced manufacturing technology, 2020)
Volumetric error is a primary factor that affects the accuracy of machining tools. The ability to ascertain volumetric error in a rapid and simple manner is of significant importance, and this can remarkably reduce the probability of temperature variation during the experiment. This study proposes a strategy for volumetric error measurement and compensation based on laser tracer for the 3-axis numerical control (NC) machining tool, and verifies the machining accuracy of a concave semi-spheroid test piece. In this study, the calibration methods employed by the laser tracer and the error separation algorithm of the machining tool are initially investigated. Following this, the accuracy of the geometric error measurement is verified using the laser interferometer. The cubic spline interpolation method is then employed to establish the tool path volumetric error model in the 3-axis NC machining tool, and the G-code modification is conducted for volumetric error compensation. Experiment results show that when the error compensation is performed, the improvement in the accuracy as compared with the initial state exceeds 50% not involving machining. To evaluate the accuracy and effectiveness of the proposed method, two machining tests to obtain a concave semi-spheroid test piece with and without volumetric error compensation strategy are studied, and the corresponding accuracies are measured by a high precision coordinate–measuring machine. It is found that the machining accuracy after having performed the error compensation is approximately 43% higher than that obtained on the pre-volumetric error compensation.